PERBEDAAN MOTIVASI BERPRESTASI ANTARA MAHASISWA AKTIVIS DAN NON AKTIVIS UKM KEROHANIAN DI UNIVERSITAS MERDEKA MALANG - Andrew Trisno (University of Merdeka Malang, 2010)
Abstract Students are the hope of the nation's younger generation who are prepared to continue the national development in the future, the students are required to perform well in various fields, including in education. High achievement motivation of a student will have an effect on academic achievement. achievement motivation is the impetus for success in a situation of competition based on the size advantages over the standard itself or others. Achievement motivation is the driving force that motivates the spirit of a person's work, because that achievement motivation would encourage someone to develop creativity and mobilize all its capabilities and energy to achieve maximal performance. UKMKerohanian is a container building and spiritual refreshment for students. Influential religion as a motivation in encouraging individuals to perform an activity, because the acts committed backgrounds religious beliefs judged to have the element of obedience, so that the presence of UKM Kerohanian activities will build spiritual maturity it is expected that individual students can be motivated also in academics included. Students who are actively involved in UKM Kerohanian is called activist of UKM Kerohanian. This study title is Achievement Motivation Differences between student activists and non-activist UKM Kerohanian at the Merdeka University of Malang. The variables in this study was achievement motivation as the dependent variable, activist and non activist UKM Kerohanian as independent variables. The hypothesis of this study were that there are differences of achievement motivation between student activists and non-activists UKM Kerohanian at Merdeka University of Malang. The sample of this study were activists student of UKM Kerohanian and non-activist UKM Kerohanian, and the total were 84 people. The sampling technique in this research using purposive sampling technique. Methods of data collection in this study using a scale of achievement motivation with a high of 72 aitem. The results of testing the validity of using the formula of Pearson product moment correlation for the scale of achievement motivation showed that there are 15 aitem aitem fall and there were 57 valid by a correlation coefficient moves from 0.218 to 0.707. Reliability Test Results using the formula shown alpha cronbach, alpha value were 0.934. This indicated that the scale of measurement or research instrument for the study variables have been reliable. The results of data analysis using the T-Test showed that the t-count of 2.987 with a significance level of 0.004, so the hypothesis have been accepted,that there are differences in achievement motivation between student activists and nonactivists UKM Kerohanian at Merdeka University of Malang. Keywords: Achievement Motivation, UKM Kerohanian.